Pengaruh Islamic Work Ethic dalam Memprediksi Work Engagement dengan Psychological Capital dan Gratitude sebagai Mediator pada Karyawan Perusahaan Bank Syariah di Indonesia - Andriana, Felannisa (UI Scholars Hub, 2025)
The rapid development of Islamic banking in Indonesia has prompted increased attention to the level of employee work engagement. Although driven by Islamic values that prioritize integrity, it is important to understand the factors that influence work engagement in Islamic banks in order to create a productive work environment that is in accordance with Islamic principles. This study aims to explain the relationship between Islamic work ethics, psychological capital, gratitude, and work engagement in the context of Islamic banking, involving Islamic banking employees in Indonesia as respondents. Data were analyzed using the Structural Equation Modeling (SEM) method. The results show a significant negative relationship between Islamic work ethics and work engagement, and gratitude does not significantly mediate this relationship. In addition, a positive relationship was found between Islamic work ethics and work engagement mediated by psychological capital, and a positive relationship between Islamic work ethicss and gratitude. The discussion concludes that Islamic work ethics combined with psychological capital has a significant role in increasing employee work engagement in Islamic banks.